MEMASYARAKATKAN KESALEHAN: Dimensi Tasawuf dalam Etika Sosial Profetik Kuntowijoyo - Kurniawan Dwi Saputra (ABHATS: Jurnal Islam Ulil Albab, 2020)
In his elaboration of Islamic science, Kuntowijoyo proposed a social ethical framework consisting of three aspects, namely humanization, liberation, and transcendence. These three elements are of social ethics from the Qur'an Surah Ali Imran 110. This idea and Kuntowijoyo's thoughts in general were very thick with a sociological element. Based on this background, this study attempts to scrutiny whether there is sufistic dimensions of in Kuntowijoyo's thought by focusing on his prophetic social ethical ideas. The research was conducted by doing content analysis of Kuntowijoyo's works and interpreting in heuristic hermeneutics way. The writer found the trilogy of humanization, liberation, and transcendence in Kuntowijoyo's thought reflects the trilogy of purification of the soul in moral Sufism, namely takhalli, tahalli and tajalli which are applied to the social realm.